Effect of Early Intravenous Immunoglobulin Therapy in Kawasaki Disease: A Systematic Review and Meta-Analysis - Yan, Fan; Zhang, Huayong; Xiong, Ruihua; Cheng, Xingfeng; Chen, Yang; Zhang, Furong (Frontiers in Pediatrics, 2020)
Background: In the latest 2017 American Heart Association guidelines for Kawasaki disease (KD), there are no recommendations regarding the early administration of intravenous immunoglobulin (IVIG). Therefore, the purpose of this systematic review and meta-analysis was to investigate the effects of early IVIG therapy on KD. Methods: We searched databases including PubMed, Medline, the Cochrane Library, and the Clinicaltrials.gov website until July 2019. Results: Fourteen studies involving a total of 70,396 patients were included. Early treatment with IVIG can lead to an increased risk of IVIG unresponsiveness [OR 2.24; 95% CI (1.76, 2.84); P = 0.000]. In contrast to studies performed in Japan [OR 1.27; 95% CI (0.98, 1.64); P = 0.074] that found no significant difference in coronary artery lesions (CAL) development , studies conducted in China [OR 0.73; 95% CI (0.66, 0.80); P = 0.000] and the United States [OR 0.50; 95% CI (0.38, 0.66); P = 0.000] showed a reduced risk in the occurrence of CAL with early IVIG treatment. Conclusions: At present, the evidence does not support treatment with IVIG in the early stage of the onset of KD. But early IVIG treatment could be a protective factor against the development of CAL , which needs to be further clarified.